The Influence of Project Based Learning (PJBL), Character Development and Learning Independence on the Implementation of the Pancasila Profile at SMK PGRI 13 Surabaya - Erfina Trie Uryanti; Siti Sri Wulandari (Economic Education Analysis Journal, 2025)
This study aims to find out how the influence of Project Based Learning (PJBL), Character Development and Learning Independence on the Pancasila Profile at SMK PGRI 13 Surabaya. This type of research uses quantitative. The population of this study is students in grades X and XI of the Department of Office Management at SMK PGRI 13 Surabaya with a sampling technique using a Saturated Sample with a sample of 113 respondents. Data collection with questionnaires. The analysis method was carried out by multiple linear analysis assisted by SPSS software version 25. The results showed that the variables Project Based Learning (PJBL), Character Development and Learning Independence had a positive and significant effect on the Pancasila Profile both partially and simultaneously. So it can be concluded that Project Based Learning (PJBL), Character Development and Learning Independence can affect the implementation of the Pancasila Profile. However, the influence of the three variables is still relatively low, so if a similar study is held, it is expected to complement various shortcomings and add other variables besides the variables used.